IN A DIFFERENT VIEW: FEMINIST CONTRIBUTION TO ECUMENICAL DIALOGUE - Canceran, Delfo C (Asian Horizons, 2019)
In ecumenical dialogue, we are witnessing a blurring of distinctions or crossing of boundaries. Ecumenical dialogue relates with the complex narratives of community life of the different churches in the world. This paper deals with the problematic of ecumenical dialogue by deriving ideas from feminist theories. Feminist theories have explored and proposed ideas on identity which we can use in ecumenical dialogue as a guidepost in relating with other churches or faiths. The discourse on identity is useful in positioning oneself in a dialogue that respects the difference or particularity of each church of faith. Churches should always recognize the limits of their reason and welcome self-critique in their knowledge. Reflective solidarity can be proposed as an appropriate way of dealing with the tension posed by ecumenical dialogue. Reflective solidarity is defined as a mutual expectation of the churches’ responsible orientation to ecumenical movement. In line with hermeneutics of difference, reflective solidarity builds from ties created by difference.